In vitro and in vivo evaluation of an intraocular implant for glaucoma treatment - Natu, Mădălina V. (2011)
Implantable disks for glaucoma treatment were prepared by blending poly(ɛ-caprolactone), PCL, poly(ethylene oxide)-b-poly(propylene oxide)-b-poly(ethylene oxide) and dorzolamide. Their in vivo performance was assessed by their capacity to decrease intraocular pressure (IOP) in normotensive and hypertensive eyes. Drug mapping showed that release was complete from blend disks and the low molecular weight (MW) PCL after 1 month in vivo. The high MW PCL showed non-cumulative release rates above the therapeutic level during 3 months in vitro. In vivo, the fibrous capsule formation around the implant controls the drug release, working as a barrier membrane. Histologic analysis showed normal foreign body reaction response to the implants. In normotensive eyes, a 20% decrease in IOP obtained with the disks during 1 month was similar to Trusopt® eyedrops treatment. In hypertensive eyes, the most sustained decrease was shown by the high MW PCL (40% after 1 month, 30% after 2 months). It was shown that the implants can lower IOP in sustained manner in a rabbit glaucoma model.